A Prospective, Randomized, Controlled Comparison of Adhesive Wound Closure Devices in an Orthopaedic Patient. (23rd September 2022) - Burke, John F.; MacLean, Ian S.; Smith, J. Michael; Hart, Joseph M.; Miller, Mark D.
Abstract : Introduction: The objective of this study was to compare Zip and Clozex with a typical closure using a running 3-0 Prolene suture. Methods: A prospective, randomized, controlled trial was conducted in patients aged 18 years and older undergoing elective orthopaedic surgical procedures between 2019 and 2021. Patients were randomized to undergo skin closure using a running 3-0 Prolene suture, Zip, or Clozex. The length and location of incision, time to close, surgeon satisfaction, and complications were recorded. The Stony Brook Scar Evaluation Scale (SBSES) was used to assess cosmesis at 2 weeks and 3 months postoperatively. Patient satisfaction and adverse events were also recorded. Results: Thirty-two patients were included in the analysis. Suture closure time was longer than Zip (266 vs 123 seconds; P = 0.02) and Clozex (266 vs 91 seconds; P = 0.005). SBSES scores were greater for Clozex at 2 weeks compared with suture (4.09 vs 2.8; P = 0.005). At 3 months, Clozex maintained greater scores compared with suture (3.82 vs 2.85; P = 0.023) and Zip (3.82 vs 3.0; P = 0.046).No differences were observed in patient satisfaction at any time points. Discussion: Although patient satisfaction was similar across groups, wound closure times, SBSES scores, and total cost favor Clozex compared with Prolene suture or Zip. ClinicalTrials.gov Registration Number: NCT05251064